Growth Performance, Liveability and Physico Chemical Properties of Broiler Chicken Fed Moringa oleifera Based Diets - Gadzirayi , C.T.; Chikwanda, A.; Tuwe, Fatima (International Journal of Poultry Science, 2022)
Objective: The study investigated the effect of Moringa oleifera on growth performance, liveability and the related physico-chemical properties of the broilers chicken. Materials and Methods: Forty-five day old broiler chicks (cobb 500) were randomly distributed into three dietary treatment groups. The treatments were T1 (control without Moringa), T2 (5% inclusion level of Moringa oleifera leaf meal) T3 (7% inclusion level of Moringa oleifera leaf meal). Clean fresh water was provided ad libitum, feed was provided according to recommended daily intake per bird. Left overs were weighed to get daily intake and feed conversion efficiency. Birds were vaccinated at the hatchery and research site. Medications were used according to disease diagnosed. Results: There was a significant effect of Moringa oleifera on weekly weight gain, feed intake and average daily gain (p<0.05). Results showed no significant effect of Moringa oleifera on final weight and feed conversion efficiency (p>0.0.05). Liveability was 100%. Diet supplemented with Moringa oleifera positively affected the physico-chemical properties, water holding capacity and colour of meat. There was no significant effect (p>0.05) on pH and marbling, although marbling tended to decrease with increase in Moringa oleifera inclusion. Conclusion: Moringa oleifera as a feed additive in broiler feed improved the feed intake, average daily gain and colour attributes (l* = lightness, a* = redness and b* = yellowness).